Bridging science and society: Developing a citizen science biomonitoring approach for river ecosystems in Italy - Samuele Roccatello; Alessandro Lagrotteria; Chiara Andrà; Alberto Doretto (Ecological Indicators)
Rivers are among the most altered and impacted freshwater ecosystems on Earth, so that collective efforts should be fuelled by professionals and societies to implement their biomonitoring and conservation. Citizen science is recognized as a powerful approach but its application in river biomonitoring is still scarce, especially in Italy. This study was aimed at developing and validating a citizen science biomonitoring approach for river ecosystems based on the analysis of benthic macroinvertebrate communities. By using a calibration dataset composed of 932 sampling events performed by professionals, a simplified macroinvertebrate community was first obtained by selecting only 36 representative taxa. Four different, but routinely applied, metrics were calculated on both the simplified and calibration communities and showed strong and significant correlations. Thresholds for the four selected metrics were statistically derived and offered a good agreement in discriminating not-impacted and impacted conditions according to the official methodology. The performance of the proposed approach was validated on ten independent sampling campaigns with citizen science volunteers and compared to benchmark sites. Since 33 out of 36 taxa were recorded at least once, results showed that the simplified macroinvertebrate community was effective and representative. The ecological status assessment and the selected metrics were generally comparable to the values of the benchmark sites, despite some differences being observed depending on the metric. This study represents one of the first efforts in the direction of developing a citizen science macroinvertebrate-based methodology for river biomonitoring in Italy and it supports the adoption of a multi-metric approach.